Effect of Starch Coating on Shelf-Life and Biochemical Properties of Daucus carota - Pokhrel, Shanta; Basnet, Bibisha; Bhattarai, Dhruba Raj; Shrestha, Anjali; Yadav, Anand Kumar; Gautam, Ishwori P (Nepal Journal of Science and Technology, 2023)
A simple root vegetable (Daucus carota), often called as carrot, is usually conical or cylindrical in shape. It has a great medicinal value and different health benefits. The main objective of the study is to evaluate the effect of starch coating on shelf-life and biochemical properties of carrot. Total soluble solid (TSS) and titrable acidity (TA) was measured by hand refractometer method. The carrot treated with calcium chloride was more acidic 0.72 (±0.075) than distilled water 0.46 (±0.086) and starch 0.48 (±0.074) at 10 days after storage. Total soluble solid was found maximum at 10 days after storage (11.9 °Brix). As measured by spectrophotometer, carrot coated with starch had considerably high β-carotene content (21.78 mg/100 g) as compared to calcium chloride (17.39 mg/100 g) and distilled water (17.19 mg/100 g). Highest physiological weight loss was exhibited by calcium chloride as compared to distilled water and starch. Shelf-life of carrot was shorter in calcium chloride as compared to distilled water and starch; longest shelf-life was exhibited by starch coated carrot.